Pengaruh Modal Intelektual Dan Struktur Kepemilikan Terhadap Nilai Perusahaan(Studi Kasus Pada Sektor Keuangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Ningtias, Jerawati; , Lukman Hakim, S.E., M.Si (2017)
The purpose of this study was to analyze the effect of intellectual capital and intellectual capital disclosures on corporate value by using Pulic (VAIC ™) to measure the performance of intellectual capital which is the independent variable and analyze the influence of the ownership structure of the ownership structure of managerial and institutional ownership structure on firm value.Data in this research is secondary data on the financial sector go public in Indonesia Stock Exchange Source data is based on ICMD (International Capital Market Directory). The sample used in this study on the financial sector companies listed on the Indonesia Stock Exchange year period 2013-2015, statistical method used is descriptive multiple regression analysis, hypothesis testing the value of the t statistic. The results obtained showed intellectual capital and intellectual capital disclosures positive and significant effect on firm value. As well as the ownership structure of managerial positive effect on firm value, and institutional ownership structure significantly influence the value company.